(untitled) (Eurasian Journal of Ecology, 2024)
Assessment of health at the present stage urgently requires the development of scientific approaches to identify early changes in the state of the organism under the influence of negative effects of production factors. It is known that the functional state of the organism at work is influenced primarily by factors of the work process that cause tension of regulatory mechanisms (nervous, humoral, metabolic) under the regulatory influence of the CNS. The study of mechanisms of regulation of enzymatic activity is one of the most important tasks in the study of metabolic processes in living organisms and in the mechanisms of their adaptation to environmental factors. Enzymes are characterised by extremely high efficiency and specificity. In every living cell hundreds of biochemical reactions are taking place continuously carrying out decomposition and oxidation of nutrients coming from outside, as a result of which energy is generated for the transformation (synthesis) of organic substances, and enzymes are catalysing the rapid progress of these biochemical reactions. Each enzyme molecule performs several thousand to several million operations per minute, while the enzyme reacts with the substrate and accelerates its transformation and remains unchanged, both qualitatively and quantitatively. The study of the influence of a complex of chemicals on the biochemical mechanism of the body of experimental animals, namely, on the enzyme profile, was carried out in the main workshops of Ust-Kamenogorsk Titanium-Magnesium Combine. In the experiment were used sexually mature white rats line "Wister". The activity of gamma-glutamyltransferase, aspartate-transferase, alanine aminotransferase, creatinine phosphokinase, lactate dehydrogenase, cholinesterase, alkaline phosphatase and alpha-amylase was determined to evaluate the changes in the enzyme profile. As a result of the experiment during exposure to a complex of toxic substances in workshops No1, No2, and No3, such as chlorine, hydrogen chloride, tetrachloride, phosgene, magnesium dichloride, changes in the enzyme status of the body of experimental animals were revealed. The revealed changes, apparently, are caused by influence of a complex of chemical substances influencing enzyme activity and biosynthesis in liver tissue. Key words: enzyme profile, experimental animals, complex chemicals.